Employee of the month - Ong, Xiao Hui (2018)
Employee of the Month is a 5 minute 2D animated short which tells the story of a regular janitor and an accomplished employee. Highlighting both the issues of authenticating one's worth with materialistic achievements and the social stigma attached to a janitorial job which society necessitates but "santimoniously disavows" (W.P.Carey Research, 2015), Employee of the Month aims to bring a reconsideration of the reward structure through a changing relationship between our typical employee and janitor.